Karakteristik Fisik dan Kimia Tepung Silase Limbah Ikan Gabus (Channa striata) dengan Penambahan Konsentrasi Tepung Kiambang Terfermentasi - Agus Supriyanto; Ace Baehaki; Siti Hanggita (Universitas Sriwijaya, 2015)
The objective of this research was to observe the physical and chemical characteristics of fish waste silage with the addition of flour Salvinia molesta. The research used the completely randomized design (CRD) with fermented flour kiambang as treatment and repeated three times. The parameters were bulk density as physical analysis, and chemical analysis (ash content, protein content, fat content and crude fiber). The results showed that different of ratio concentration Salvinia molesta flour had significant effect on bulk density, protein content, fat content, crude fibre and but didn’t give significant effect on ash content.